2022
DOI: 10.3390/prosthesis4030037
|View full text |Cite
|
Sign up to set email alerts
|

The Conometric Connection for the Implant-Supported Fixed Prosthesis: A Narrative Review

Abstract: Aim: The conometric concept was proposed as a possible connection between the abutment and the prosthetic coping. This research aimed to review the features and possible clinical uses of this connection in an implant-supported fixed prosthesis. Methods: An electronic search was conducted on an online database for the topic in object; articles published in international literature were considered and the research gave 17 results, and 6 parameters were analyzed. Results: This connection eliminated the possibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 37 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…A conometric prosthetic restoration system has been reported by some authors as a means to fix the prosthetic restoration to the abutment, obviating the use of retention through the use of screws or cement. The use of this technique offers very good clinical results; however, while we were able to find relevant histomorphometric evidence of the good performance of peri-implant crestal bone [29], no definitive evidence of the 3D structure of peri-implant connective tissues around conometric prosthetic restorations has been documented.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…A conometric prosthetic restoration system has been reported by some authors as a means to fix the prosthetic restoration to the abutment, obviating the use of retention through the use of screws or cement. The use of this technique offers very good clinical results; however, while we were able to find relevant histomorphometric evidence of the good performance of peri-implant crestal bone [29], no definitive evidence of the 3D structure of peri-implant connective tissues around conometric prosthetic restorations has been documented.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, by not having to remove cement residues, it is possible to set the margins in more apical portions, improving the aesthetics of the restorations. It has also been proven that retentive force is adequate for fixed rehabilitation even after a high number of insertiondisengagement cycles [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the clinical benefits, the efficiency of laser sintering and laser melting in the production of prosthetic elements promises to reduce time and costs [33,34]. This is a win-win situation, as it improves the convenience and accessibility of these advanced techniques for practitioners and translates into more convenient solutions for patients [35]. Digital tools and computerized planning of implant-prosthetic rehabilitation represent the fundamental pillars of modern dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…[24,25] In vitro analyses have demonstrated that in a conometric connection, there is no presence of bacteria on the interface between the cap and abutment, [26,27] and in vivo studies have evaluated the success rate of the conometric connection, showing a rate of 97.77% or 100% over a follow-up period of more than 2 years. [23,28,29] Other numerical studies have indicated that the retention force is inversely proportional to the taper angle of the cap. [30,31] Specifically, they have established that the conometric connection is activated with an impulsive force of 40/36 N for a taper angle of 6°and 235 N for a taper angle of 1°.…”
Section: Introductionmentioning
confidence: 99%